Electronic Business Factors in Building Online Consumer Loyalty on E-commerce Platforms - Hasdiansa, Ilma Wulansari; Hasbiah, Sitti (International Humanity Advance, Business & Sciences, 2024)
In the thriving Indonesian retail market, companies are leveraging digital marketing to broaden their market presence, giving rise to various online shopping websites. This strategic shift aims to offer unique differentiators and create distinct value propositions. Central to this digital marketing approach is the goal of cultivating customer loyalty, which is crucial for increasing purchase intention and stimulating word-of-mouth referrals. This research focuses on the Indonesian retail sector's integration of e-commerce services, specifically investigating the effects of eight e-business factors on the development of e-commerce customer loyalty (e-loyalty). The study's findings emphasize the importance of customization, contact interactivity and convenience, which are key dimensions of e-business factors, in positively influencing e-loyalty. This research underscores the evolving dynamics of digital marketing in retail and the critical role of specific e-business elements in building a loyal customer base in the competitive online marketplace.